A new hERG allosteric modulator rescues genetic and drug‐induced long‐QT syndrome phenotypes in cardiomyocytes from isogenic pairs of patient induced pluripotent stem cells - Luca Sala; Zhiyi Yu; Dorien Ward‐van Oostwaard; Jacobus PD van Veldhoven; Alessandra Moretti; Karl‐Ludwig Laugwitz; Christine L Mummery; Adriaan P IJzerman; Milena Bellin (EMBO Molecular Medicine)
Abstract Long‐QT syndrome (LQTS) is an arrhythmogenic disorder characterised by prolongation of the QT interval in the electrocardiogram, which can lead to sudden cardiac death. Pharmacological treatments are far from optimal for congenital forms of LQTS, while the acquired form, often triggered by drugs that (sometimes inadvertently) target the cardiac hERG channel, is still a challenge in drug development because of cardiotoxicity. Current experimental models in vitro fall short in predicting proarrhythmic properties of new drugs in humans. Here, we leveraged a series of isogenically matched, diseased and genetically engineered, human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) from patients to test a novel hERG allosteric modulator for treating congenital LQTS, drug‐induced LQTS or a combination of the two. By slowing IKr deactivation and positively shifting IKr inactivation, the small molecule LUF7346 effectively rescued all of these conditions, demonstrating in a human system that allosteric modulation of hERG may be useful as an approach to treat inherited and drug‐induced LQTS. Furthermore, our study provides experimental support of the value of isogenic pairs of patient hiPSC‐CMs as platforms for testing drug sensitivities and performing safety pharmacology.